Formula Latihan Teknik Tangan Kanan dalam Gitar Klasik: Shearer, Parkening, dan Werner - Birul Walidaini (Universitas Negeri Surabaya, 2020)
Classical guitar developed until now. Aspects and the surrounding area have also experienced developments such as the creation of new compositions, innovation in guitar construction, and the holding of performances that accommodate classical guitar. However, the author tries to raise another area that is quite important in learning classical guitar, namely the teaching method. Along with the development of the times and technology, the basic methods of learning classical guitar are becoming less attention. This article aims to dissect the most basic classical guitar methods and are limited to techniques and instructions for the right hand. This research is a descriptive study with a qualitative design and the classical guitar method book document as an object. The objects raised are the classic Classic Guitar Technique from Aaron Shearer (1963), The Christoper Parkening Guitar Method, Vol. 1 (1997), and the Classical Guitar Method from Bradford Werner (2017). The results of this study present the formula of each method offered to train the right hand in playing classical guitar in their own way. In closing, the authors hope that the classical guitar method remains the basis for learning classical guitar and is further developed in the future.Keywords: classical guitar, right hand, classical guitar method